Binding of a cell-type-specific RNA splicing factor to its target regulatory sequence. - Nandabalan, K (1995)
The transcript of the Saccharomyces cerevisiae MER2 gene is spliced efficiently during meiosis but not during vegetative growth. Efficient splicing of the wild-type MER2 transcript requires the Mer1 protein, which is produced only in meiotic cells. Analysis of deletion and substitution mutations in the MER2 5' exon demonstrates that the unusually large size of this exon plays an important role in splicing regulation. The cis-acting sequences essential for Mer1-dependent splicing of MER2 RNA were determined by the analysis of MER2 deletion mutants and hybrid genes. The 80-base MER2 intron is sufficient for Mer1-dependent splicing in vivo, but sequences in the 5' exon enhance splicing efficiency. The Mer1 protein contains the KH motif found in some RNA-binding proteins, and RNA gel mobility shift assays demonstrate that Mer1 binds specifically to MER2 RNA. Both the transcript derived from the intronless MER2 gene and the transcript consisting only of the intron are able to bind to Mer1 in vitro, but neither has as high affinity for the protein as the intact substrate. RNase T1 footprinting indicates that the Mer1 protein contacts MER2 RNA at several points in the 5' exon and in the intron. Thus, Mer1 interacts directly with a regulatory element in MER2 RNA and promotes splicing.